2017
DOI: 10.1109/jtehm.2017.2672965
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Radiofrequency Field Treatment to Produce Hepatic Hyperthermia: Efficacy and Safety in Swine

Abstract: The Kanzius non-invasive radio-frequency hyperthermia system (KNiRFH) has been investigated as a treatment option for hepatic hyperthermia cancer therapy. The treatment involves exposing the patient to an external high-power RF (13.56 MHz) electric field, whereby the propagating waves penetrate deep into the tumor causing targeted heating based on differential tissue dielectric properties. However, a comprehensive examination of the Kanzius system alongside any associated toxicities and its ability to induce h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…7a, b) yielded a calculated relative heating rate of liver, tumor, and fat as shown in Figure 8 (utilizing tissue mass density of ρ liver = ρ tumor = 1.06 g/mL and ρ fat = 0.9 g/mL) by electromagnetic energy in the radiofrequency-microwave spectrum. The relative heating rate was calculated using the simplified infinite tissue layer approximation as previously described [33]. Using this model, the difference in calculated heating rate between liver and tumor tissues did not exceed 3.5% for the measured frequency spectrum from 10 to 1,000 MHz, whereas the heating rate of fat was approximately 5-6 times greater than that of liver and tumor tissues, similar to our previous study [33].…”
Section: Permittivitysupporting
confidence: 81%
See 1 more Smart Citation
“…7a, b) yielded a calculated relative heating rate of liver, tumor, and fat as shown in Figure 8 (utilizing tissue mass density of ρ liver = ρ tumor = 1.06 g/mL and ρ fat = 0.9 g/mL) by electromagnetic energy in the radiofrequency-microwave spectrum. The relative heating rate was calculated using the simplified infinite tissue layer approximation as previously described [33]. Using this model, the difference in calculated heating rate between liver and tumor tissues did not exceed 3.5% for the measured frequency spectrum from 10 to 1,000 MHz, whereas the heating rate of fat was approximately 5-6 times greater than that of liver and tumor tissues, similar to our previous study [33].…”
Section: Permittivitysupporting
confidence: 81%
“…Hyperthermia is thought to potentiate both chemo-and radiation therapy in the treatment of malignancies [36,37]. Using the simplified approximation of infinite tissue planes, we have previously shown that subcutaneous fat heats at a rate 5.8-to 7.3-fold greater than liver tissue at an exposure frequency of 10-3,000 MHz [33]. In the current study, the heating rates were calculated for liver, tumor, and fat tissues for the frequency range of 10-1,000 MHz as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, excessive temperatures (hot spots) can occur at tissue interfaces, and due to the orientation of the main electric field component, which is perpendicular to fat layers, especially excessive heating of fat tissue can be treatment limiting when using this technique [27][28][29]. Therefore, capacitive heating becomes less effective with increasing thickness of the fat layer and heating of deep-seated tumors can be challenging [30][31][32].…”
Section: Capacitive Radiofrequency Heatingmentioning
confidence: 99%
“…In industrial use, aluminum melting technique using induction heating is typical, contributing to energy saving and safety improvement of factory equipment [2]- [4]. As a typical example of medical applications, induction heating technology is used in thermotherapy equipment for cancer (hyperthermia) [5]- [6]. For home appliances, it is widely used in cooktops [7]- [10].…”
Section: Introductionmentioning
confidence: 99%